Generation of T. aestivum x Ae. speltoides doubled amphiploids for future use in heat tolerance research, and analysis of their clonality - McGowan, Jessica (Kansas State University, 2016)
Wheat is increasing in importance as the global population rises; therefore, abiotic stresses adversely affecting wheat yield, such as heat stress, are of growing concern. Accessions of Aegilops speltoides, a relative of the ancestral donor of the B genome of hexaploid wheat (Triticum aestivum), have been determined to be highly heat tolerant. Six Ae. speltoides accessions were used as male donors in crosses with six hexaploid wheat lines, in all combinations, to obtain F1 amphiploid seed (ABDS = 28 chromosomes). The F1 seedlings were treated with a colchicine solution to achieve chromosome doubling (AABBDDSS = 56 chromosome doubled amphiploids) and grown out to maturity. S1 seed was collected for optimal or heat treatment after anthesis and SPAD readings were taken daily during treatment until maturity. In addition to physiological measurements, leaf tissue samples were collected from S1 plants and their respective parents for marker sequence analysis. Certain doubled amphiploids survived longer in heat treatment than their wheat parents with similar SPAD readings, but had a longer maturation time, similar to their Ae. speltoides parents. S2 seed was collected from 20 S1 plants, including one plant from the heat treatment. This heat screen demonstrates variation among the amphiploids, the genetic diversity within pedigree warrants further investigation into the viability and heat stress tolerance of the S2 seeds obtained from this experiment.
Keywords: Wheat; Wheat ancestors; Amphiploid; Doubled amphiploid; Aegilops speltoides; Heat tolerance